PENGENALAN MEDIA GAME BLOOKET DALAM PEMBELAJARAN SENI BUDAYA DI SMP NEGERI 10 SEMARANG - Azzahro, Khoirun Nisa’; Nugrahani, Rahina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cultural Arts education in schools still tends to rely on conventional methods, resulting in low student engagement and participation, particularly in the delivery of theoretical material. Therefore, more interactive and engaging instructional media are needed. One alternative that can be utilized is digital educational games such as Blooket. This study aims to describe the process of introducing Blooket as a learning medium in Cultural Arts education at SMP Negeri 10 Semarang, to examine students’ responses to its use, and to identify its potential as a learning medium. This study employs a descriptive qualitative approach using a case study method, with students at SMP Negeri 10 Semarang as the subjects. Data were collected through observation, interviews, and documentation, while data analysis employed the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of Blooket was carried out in three stages: preparation, implementation, and evaluation. The use of this platform increased student engagement, as reflected in their active participation and enthusiasm during the learning process. In addition, students’ responses were positive, as the learning experience became more engaging, enjoyable, and supportive of their understanding of the material. Despite challenges such as limited devices and internet connectivity, Blooket demonstrates strong potential as an interactive and effective learning medium for improving the quality of Cultural Arts education.